High-Precision Micromachining of Sapphire Towards Optical Waveguiding Structures using Femtosecond Lasers - Kefer, Stefan; Zettl, Julian; Schmauß, Bernhard; Esen, Cemal; Hellmann, Ralf (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
While sapphire is one of the most durable materials, its properties entail that high-precision machining, especially in the sub-millimeter regime, is still challenging. This contribution demonstrates and discusses novel femtosecond laser-based micromachining approaches for the fabrication of rotational-symmetric sapphire workpieces, specifically the generation of optical fibers by means of laser lathe of sapphire rods and the practical realization of windmill fibers. In addition, volume refractive index modification in planar sapphire substrates is presented to induce photonic crystal waveguides. The micromachined structures are comprehensively examined with respect to geometric fidelity, surface roughness, refractive index modification, and potential optical waveguiding properties. All micromachining approaches are done by means of frequency-doubled or frequency-tripled femtosecond laser radiation. Different laser optical setups including laser scanning head, spatial beam profilers including a spatial light modulator and axial rotatory movement of the specimen are employed for micro structuring and in-depth refractive index modifications. In particular for laser lathe, a sophisticated scanning pattern, in combination with an incremental axial rotatory movement of the specimen, allows for the precise diameter reduction of sapphire rods with 250 µm diameter to fibers with outer diameters of 25 µm. By supporting the workpiece with a V-groove fixture, multi-mode fibers with lengths up to 20 cm can be processed with an average surface roughness of 250 nm. Additionally, an adapted ablation scanning sequence enables the first practical demonstration of sapphire windmill fibers. Furthermore, using a spatial light modulator allows for the adaption of the laser propagation properties as to enable volume refractive index modifications with free-form arrangement. Hexagonal patterns of refractive index modifications surrounding a pristine waveguide core are fabricated and single-mode waveguiding at 1550 nm is verified. Finally, the possibility of integrating Bragg gratings into this photonic waveguide type is demonstrated.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Femtosecond Laser; Laser Lathe; Micromachining; Optical Waveguiding; Refractive Index Modification; Rod-to-Fiber; Sapphire